CONTINUOUS PROFESSIONAL DEVELOPMENT BASED ON INTERNAL COACHING IN SCHOOL INSTITUTIONS - Hikmawati Risa; Nurjannah , Nurjannah; Utomo, Erry (Faculty of Teacher Training and Education, Mulawarman University, 2023)
Continuous professional development is a program carried out to improve teacher competencein carrying out their duties. The fact shows that implementing continuous professionaldevelopment has not significantly improved teacher professionalism. This program has notbeen running consistently, due to a lack of internal motivation from teachers who tend not toplay an active role in the culture of independent learning, because they still position themselveswaiting for professional development activities from external parties to improve theircompetence. This study aims to develop a model of continuous professional developmentthrough school institutions based on internal coaching. Internal coaching is the basic capital forteachers to become lifelong learners and self-directed for increasing competency. The researchwas conducted through a development method using the Smith and Ragan model implementedin an integrated Islamic elementary school that has implemented continuous professionaldevelopment programs for almost two years, since 2019. The constructed hypothetical model isa continuous professional development model based on internal coaching through thestimulation of reflective, participatory, innovative, and collaborative abilities integrated into theschool system to form a culture of independent learning for teachers. The implication ofresearch for further development of teacher empowerment at the school level.